2012
DOI: 10.1111/j.1420-9101.2012.02562.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological adaptation along environmental gradients and replicated hybrid zone structure in swordtails (Teleostei:Xiphophorus)

Abstract: Local adaptation is often invoked to explain hybrid zone structure, but empirical evidence of this is generally rare. Hybrid zones between two poeciliid fishes, Xiphophorus birchmanni and X. malinche, occur in multiple tributaries with independent replication of upstream‐to‐downstream gradients in morphology and allele frequencies. Ecological niche modelling revealed that temperature is a central predictive factor in the spatial distribution of pure parental species and their hybrids and explains spatial and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
105
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(106 citation statements)
references
References 106 publications
(209 reference statements)
1
105
0
Order By: Relevance
“…Rather than emphasizing the uncertain threat posed by the presence of hybrid individuals, the focus should be on understanding those environmental and anthropogenic factors related to the position, structure, and dynamics of hybrid zones (Culumber et al. 2012). …”
Section: Resultsmentioning
confidence: 99%
“…Rather than emphasizing the uncertain threat posed by the presence of hybrid individuals, the focus should be on understanding those environmental and anthropogenic factors related to the position, structure, and dynamics of hybrid zones (Culumber et al. 2012). …”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have found increasing evidence for spatial structuring across numerous ecological gradients, including temperature gradients (Culumber et al. 2012), vegetation/substrate gradients (Shurtliff et al. 2013), bioclimatic gradients (Tarroso 2014), and elevational gradients (DuBay and Witt 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid zones often occur along ecological gradients, as transitional habitats may facilitate contact between species occupying different ecological niches (Culumber et al. 2012). In cases of environment‐dependent selection, the spatial distribution of individuals within a hybrid zone should correlate strongly with their genotypes (Arnold 1997; Johnston et al.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a common pattern is that warmer, low-elevation stream communities are broadly and repeatedly invaded (14, 17) whereas colder, high-elevation streams are less altered and often serve as refugia for native species tolerant of cold temperatures (18,19). The same is true regarding more subtle genetic invasions and introgressive hybridization, because many genetically pure populations exist in headwater streams where climatic conditions limit the upstream expansion of hybrid zones (20,21).The ubiquity of isolated populations of many species in mountain headwaters (14, 18, 19) suggests they have existed for extended periods, but climate-induced stream warming (22, 23) raises legitimate concerns about their future persistence. Concerns are heightened by evidence of faster air temperature increases at high elevations (24), and by model predictions that streams in snowmelt-dominated landscapes will be highly sensitive (i.e., large stream Δ°C/air Δ°C) to air temperature increases (25)(26)(27).…”
mentioning
confidence: 99%
“…As a result, a common pattern is that warmer, low-elevation stream communities are broadly and repeatedly invaded (14, 17) whereas colder, high-elevation streams are less altered and often serve as refugia for native species tolerant of cold temperatures (18,19). The same is true regarding more subtle genetic invasions and introgressive hybridization, because many genetically pure populations exist in headwater streams where climatic conditions limit the upstream expansion of hybrid zones (20,21).…”
mentioning
confidence: 99%